Innovation policy and performance of Eastern European countries - James S. Foreman-Peck; Peng Zhou (Cardiff University, Cardiff Business School, 2021)
This paper shows that EU and national innovation subsidy policies stimulated Central and East-ern Europe Countries (CEEC) productivity in the years after their entry to the EU. However, the average effectiveness of national funding was higher for the Western control group coun-tries than for the CEEC sample. EU innovation subsidies partly compensated the CEEC for the greater innovation effectiveness and impact of western economies. Although they crowded out innovation projects or funding of local governments at the country level, the subsidies crowded in national and local projects at the firm level. Local/regional state innovation aid to enterprises encouraged no increase in labour productivity in all but one of sample CEEC countries. These impacts are assessed in a sequential structural econometric model estimated using Eurostat's collection of Community Innovation Surveys covering the years 2006-2014.
Keywords: L53; L21; H71; H25; 330; innovation policy; European Union; R&D; subsidies